Web-mapping Applications for Accessing Library Collections: Case Studies using ESRI’s ArcIMS at the National Library of Scotland - Fleet, Christopher (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2005)
For several decades, map libraries and our users have appreciated the value of graphical search methods, and the integrating power of geographical coordinates for spatial searching (Van de Waal, 1974; Larsgaard, 1978). More recently there have been developments in software and data availability to allow the more widespread practical implementation of web-based graphical search tools, using dynamic maps and geo-referenced records. This year, the National Library of Scotland (NLS) has implemented pilot web-based applications using ESRI’s ArcIMS software, to provide an online spatial search method for NLS collections. This paper describes the background to these applications, the software and hardware used, interfaces developed, and I will end with an examination of the problems and prospects of this web-mapping technology.